CERITA LISAN DUA ORANG SUNAN BERADU JAGO DALAM KAJIAN STRUKTURAL DAN FUNGSI ALAN DUNDES - Dr. Mohammad Kanzunnudin, M.Pd. (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2020)
AbstractA research about "Dua Orang Sunan Beradu Jago" (a.k.a. Two Sunan Compete The Roaster)  aimed to find out and analyze a series of motives and functions based on Dundes’ theory. This study used descriptive qualitative method. The steps taken, analyzing the oral story "Dua Orang Sunan Beradu Jago" using a series of motives and functions based on Alan Dundes' theory. Data collection techniques through literature study, observation, in-depth interviews, recording, shooting, and transcription. The data analysis techniques by reducing, presenting data, and drawing conclusions. The results showed that the story "Dua Orang Sunan Beradu Jago" has six combinations of Dundes’ motives, which are (1) lacking, (2) interdiction, (3) violation, (4) consequences, (5) attempted escape), and (6) lack of liquidated. The functions include (1) educational tools, (2) solidarity of a group, (3) social sanctions and punishment, (4) social criticism, and (5) solace.